A Path-Corrected Wall Model for Ray-Tracing Propagation Modeling - Teh, C. H.; Kung, F.; Chuah, H. T. (2006)
This paper presents a path-correction technique for modeling finite-thickness walls in a ray-tracing framework without increasing its complexity. The walls are treated as infinitesimally thin slabs in ray-tracing. Using a path-correction technique, the effect of wall thickness is included in the computation of reflection and transmission coefficients. Simulation results of the proposed wall model are shown to agree closely to that of Finite-Difference Time-Domain (FDTD) simulation.